Haptics: Science, Technology, Applications 12th International Conference, EuroHaptics 2020, Leiden, The Netherlands, September 6-9, 2020, Proceedings - Nisky, Ilana; Hartcher-O'Brien, Jess; Wiertlewski, Michaël; Smeets, Jeroen (Information Systems and Applications, incl. Internet/Web, and HCI, 2020)
This open access book constitutes the proceedings of the 12th International Conference on Human Haptic Sensing and Touch Enabled Computer Applications, EuroHaptics 2020, held in Leiden, The Netherlands, in September 2020. The 60 papers presented in this volume were carefully reviewed and selected from 111 submissions. The were organized in topical sections on haptic science, haptic technology, and haptic applications. This year's focus is on accessibility. .